Sources and behaviour of nitrogen compounds in the shallow groundwater of agricultural areas (Poyang Lake basin, China); Journal of Contaminant Hydrology; Vol. 202 - Soldatova E. A. Evgeniya Aleksandrovna; Guseva N. V. Natalia Vladimirovna; Sun Zh. Zhanxue; Bychinsky V. A. Valery Alekseevich; Boeckx P. Pascal; Gao B. Bai (2017, 2017)
Title screen